Increased CXCL4 expression in hematopoietic cells links inflammation and progression of bone marrow fibrosis in MPN - Gleitz, Hélène; Dugourd, Aurélien; Sáez Rodríguez, Julio (Blood, 2020)
In primary myelofibrosis (PMF), bone marrow fibrosis is driven by normal stromal cells in the context of hematopoietic stem cells (HSCs) that carry myeloprolife